2009
DOI: 10.1295/polymj.pj2008301
|View full text |Cite
|
Sign up to set email alerts
|

Phase Structure and Mechanical Property of Blends of Organosolv Lignin Alkyl Esters with Poly(ε-caprolactone)

Abstract: Organosolv lignin (OSL) alkyl esters (carbon number n, 2-5) were synthesized by homogeneous reaction with different acyl anhydrides/4-dimethylamino pyridine in pyridine solution. Miscibility of the esterified OSL with poly("-caprolactone) (PCL) was investigated through DSC, morphological observation, and spectroscopy. DSC revealed a composition-dependent shift in T g for blends of OSL esters (n ¼ 3{5) with PCL; thus these three systems can be regarded as miscible on a T g -detection scale. AFM indicated that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…Among various lignin derivatives blends of lignin esters with synthetic polymers have been extensively studied. 161 It can thus be concluded that the miscibility improves with an increase in the chain length of the ester group. 161 The blends of OSL acetate (OSL-Ac), propionate (OSL-Pr), butyrate (OSL-Bu) and valerate (OSL-Va) have been examined.…”
Section: Equation 1 A) Lu Weiss Equation B) Gordon-taylor Equation Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Among various lignin derivatives blends of lignin esters with synthetic polymers have been extensively studied. 161 It can thus be concluded that the miscibility improves with an increase in the chain length of the ester group. 161 The blends of OSL acetate (OSL-Ac), propionate (OSL-Pr), butyrate (OSL-Bu) and valerate (OSL-Va) have been examined.…”
Section: Equation 1 A) Lu Weiss Equation B) Gordon-taylor Equation Cmentioning
confidence: 99%
“…161 The blends of OSL acetate (OSL-Ac), propionate (OSL-Pr), butyrate (OSL-Bu) and valerate (OSL-Va) have been examined. Among various lignin derivatives blends of lignin esters with synthetic polymers have been extensively studied.…”
Section: Equation 1 A) Lu Weiss Equation B) Gordon-taylor Equation Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Kubo and Kadla reported a blend of poly(ethylene oxide) with OL which showed good thermal and mechanical properties, resulting from the unique chemical structure of lignin. Teramoto et al reported a blend of poly(ε‐caprolactone) with alkylated OL which exhibited a miscible blend when the length of the alkyl chains attached to OL increased.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have blended lignin derivatives with other thermoplastic polymers. Different lignin alkyl esters were blended with thermoplastic CAB, PCL, PVAc, and PVP, mainly resulting in multiphase systems. However, thermal analysis showed good miscibility with PVP and PCL, naturally differing with derivative type.…”
Section: Lignocellulosic Biomassmentioning
confidence: 99%